An experimental study of a continuous Japanese-English auction for the wallet game - Konstantinos Georgalos; Ricardo Gonçalves; Indrajit Ray; Sonali SenGupta (Queen's University Belfast, Queen's Business School, 2026)
This paper reports results from a laboratory experiment on a continuous Japanese-English auction in a common-value 'wallet game'. The main objective is to test whether bidders follow the equilibrium bidding strategy predicted by theory. We find systematic deviations from equilibrium behaviour: instead of bidding according to the Nash equilibrium, subjects appear to rely on expected value (EV) bidding. As a consequence, observed auction prices are higher than the theoretical benchmark, and the winner's curse occurs in a substantial fraction of auctions. We analyse bidding behaviour in detail and discuss the implications of our findings.
Keywords: C72; C91; C92; D63; D83; 330; Japanese-English auction (JEA); Wallet game; Continuous bids; Winner's curse; Expected value bidding